Effects of pentoxifylline and n-acetylcysteine on injuries caused by ischemia and reperfusion splanchnic organs in rats - Cerqueira, N. Freire [UNESP]; Hussni, C. A. [UNESP]; Yoshida, Winston Bonetti [UNESP]; Sequeira, J. Lopes [UNESP]; Padovani, Carlos Roberto [UNESP] (Edizioni Minerva Medica, 2008)
Aim. Occlusion and reperfusion of splanchnic arteries cause local and systemic changes due to the release of cytotoxic substances and the interaction between neutrophils and endothelial cells. This study evaluated the role of pentoxifylline (PTX) and n-acetylcysteine (NAC) in the reduction of ischemia, reperfusion shock and associated intestinal injury.Methods. Sixty rats were divided into 6 groups of 10 animals. Rats in three groups underwent mesenteric ischemia for 30 minutes followed by 120 minutes of reperfusion, and were treated with saline (SAL-5 mL/kg/h), pentoxifylline (PTX-50 mg/kg) or n-acetylcysteine (NAC-430 mg/kg/h). The other 3 groups underwent sham ischemia and reperfusion (I/R) and received the same treatments. Hemodynamic, biochemical and histological parameters were evaluated.Results. No significant hemodynamic or intestinal histological changes were seen in any sham group. No histological changes were found in the lung or liver of animals in the different groups. There was a progressive decrease in mean arterial blood pressure, from mean of 111.53 mmHg (30 minutes of ischemia) to 44.30 +/- 19.91 mmHg in SAL-I/R, 34.52 +/- 17.22 mmHg in PTX-I/R and 33.81 +/- 8.39 mmHg in NAC-I/R (P<0.05). In all I/R groups, there was a progressive decrease in: aortic blood flow, from median baseline of 19.00 mL/min to 2.50 +/- 5.25 mL/min in SAL-I/R; 2.95 +/- 6.40 mL/min in PTX-I/R and 3.35 +/- 3.40 mL/min in NAC-I/R (P<0.05); in the heart rate, from mean baseline of 311.74 bpm to 233.33 +/- 83.88 bpm in SAL-I/R, 243.20 +/- 73.25 bpm in PTX-I/R and 244.92 +/- 76.05 bpm in NAC-I/R (P<0.05); and esophageal temperature, from mean baseline of 33.68 degrees C to 30.53 +/- 2.05 degrees C in SAL-I/R, 30.69 +/- 2.21 degrees C in PTX-I/R and 31.43 +/- 1.03 degrees C in NAC-I/R (P<0.05). In the other hand, there was an attenuation of mucosal damage in the small intestine of the animals receiving PTX, and only in the ileum of the animals receiving NAC. No changes were found in ileum or plasma malondialdehyde levels in any group.Conclusion. PTX was more efficient in reducing histological lesions than NAC, but neither treatment prevented hemodynamic changes during splanchnic organs I/R.
Keywords: Intestine, small; Ischemia; Reperfusion injury; Shock